Criminal law policy against cyberbullicide - Gusti Agung Arya Suryaningrat; Bima Kumara Dwi Atmaja (The International Journal of Politics and Sociology Research, 2023)
The purpose of writing this article is to find out the criminal law policies against cyberbulicide and how to formulate cyberbulicide in the future. This writing uses the normative legal research method where the study uses collecting and examining or tracing documents or also called using document and literature studies which aim to obtain information related to the needs in reviewing this research. In the regulation of bullying through social media that results in suicide victims or what is known as Cyberbulicide in Indonesia, there is a void in the norms in the current ITE Law, a void in the understanding, elements, and criminal charges against someone who commits cyberbullying which causes the victim to commit suicide. Meanwhile, the element of encouraging someone to commit suicide is regulated in the Criminal Code in Article 345 concerning advocating suicide, but this regulation does not reach the cyber realm. So that it is necessary to regulate Cyberbullyicide in Indonesia so that there are no more victims due to Cyberbullying. In order to provide certainty, protection and law enforcement in Cyberbulicide crime, it can be done by reforming the criminal law against criminal offenses for Cyberbulicide perpetrators. The renewal of the criminal law was carried out by considering comparisons from other countries that have Cyberbullicide regulations and taking into account the problems in the Ius Constitutum. however, these arrangements do not extend to the realm of cyber. So that it is necessary to regulate Cyberbullyicide in Indonesia so that there are no more victims due to Cyberbullying. To provide certainty, protection and law enforcement in cyberbulliicide crimes, criminal law reform can be carried out against criminal offenses for cyberbullicide perpetrators.